2011
DOI: 10.1111/j.1365-2672.2011.05127.x
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of lignified secondary cell walls of lucerne (Medicago sativa L.) by rumen fungi growing in methanogenic co-culture

Abstract: Aims:  To compare the abilities of the monocentric rumen fungi Neocallimastix frontalis, Piromyces communis and Caecomyces communis, growing in coculture with Methanobrevibacter smithii, to colonize and degrade lignified secondary cell walls of lucerne (alfalfa) hay. Methods and Results:  The cell walls of xylem cylinders isolated from stems of lucerne contained mostly xylans, cellulose and lignin together with a small proportion of pectic polysaccharides. All of these major components were removed during incu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…We found that fungi were mostly abundant on forage samples (WS, AH), in agreement with other authors who reported high abundances in sheep fed high forage-based diets (Fonty and Grenet 1994;Denman and McSweeney 2006). Rumen fungi colonize preferentially lignocellulosic tissues, and break down polysaccharide-lignin linkages thanks both to the secretion of active esterases, but also to physical disruption of fibre because of the extension of a complex rhizoidal network (Fonty et al 1999;Bootten et al 2011).…”
Section: Discussionsupporting
confidence: 92%
“…We found that fungi were mostly abundant on forage samples (WS, AH), in agreement with other authors who reported high abundances in sheep fed high forage-based diets (Fonty and Grenet 1994;Denman and McSweeney 2006). Rumen fungi colonize preferentially lignocellulosic tissues, and break down polysaccharide-lignin linkages thanks both to the secretion of active esterases, but also to physical disruption of fibre because of the extension of a complex rhizoidal network (Fonty et al 1999;Bootten et al 2011).…”
Section: Discussionsupporting
confidence: 92%
“…Differences in the relative proportions of CAZyme transcripts predicted to be involved in cellulose, hemicellulose, and pectin saccharification could help decrease direct competition for finite resources in the rumen and facilitate the co-existence of multiple genera of anaerobic fungi in the gut. A study by Bootten et al ( 2011 ) found that different genera of anaerobic fungi were able to colonize and degrade lignified secondary plant cell walls with differing efficiency and specificity. N. frontalis and P. communis were highly efficient at degrading all plant cell wall structures whereas Caecomyces communis preferentially degraded xylem tissues and was much less efficient than the other two genera studied (Bootten et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Protozoa and fungi, although far less abundant than the bacteria and archaea in terms of cell numbers, can make up approximately half of the total rumen microbial biomass [15]. Until recently, species identification and physiological characteristics of fungal and ciliate communities colonising the gastrointestinal tracts of herbivores have typically been assessed by using microscopy [16],[17] and cultivation-based techniques [18],[19]. Liggenstoffer et al .…”
Section: Introductionmentioning
confidence: 99%